Effect of nutrition‐based prehabilitation on the postoperative outcomes of patients with esophagogastric cancer undergoing surgery: A systematic review and meta‐analysis - Yi Shen; Zhuangzhuang Cong; Qiyue Ge; Hairong Huang; Wei Wei; Changyong Wang; Zhisheng Jiang; Yuheng Wu (Cancer Medicine, 2024)
Abstract Background Meta‐analyses have primarily focused on the effects of exercise‐based prehabilitation on postoperative outcomes and ignored the role of nutritional intervention. In this study, we filled this gap by investigating the effect of nutrition‐based prehabilitation on the postoperative outcomes of patients who underwent esophagectomy and gastrectomy. Methods Five electronic databases, namely, PubMed, the Web of Science, Embase, Cochrane Library, and CINAHL, were searched. Adults diagnosed with esophagogastric cancer who were scheduled to undergo surgery and had undergone uni‐ or multimodal prehabilitation, with at least a week of mandatory nutritional intervention, were included. Forest plots were used to extract and visualize the data from the included studies. The occurrence of any postoperative complication was considered the primary endpoint. Results Eight studies met the eligibility criteria, with five randomized controlled trials (RCTs) and three cohort studies. In total, 661 patients were included. Any prehabilitation, that is, unimodal (only nutrition) and multimodal prehabilitation, collectively decreased the risk of any postoperative complication by 23% (95% confidence interval [CI] = 0.66–0.90). A similar effect was exclusively observed for multimodal prehabilitation (risk ratio [RR] = 0.78, 95% CI = 0.66–0.93); however, it was not significant for unimodal prehabilitation. Any prehabilitation significantly decreased the length of hospital stay (LOS) (weighted mean difference = −0.77, 95% CI = −1.46 to −0.09). Conclusions Nutrition‐based prehabilitation, particularly multimodal prehabilitation, confers protective effects against postoperative complications after esophagectomy and gastrectomy. Our findings suggest that prehabilitation slightly decreases LOS; however, the finding is not clinically significant. Therefore, additional rigorous RCTs are warranted for further substantiation.